Immunity and protection of SARS-CoV-2DNA and protein vaccines - LIU XIAOJUAN; LI ZHIHUA; XIAO HONGJIAN; BI YANWEI; LI YUZHONG; LU SHAN; LI QIHAN; CUN WEI (2023)
A DNA vaccine against SARS-CoV-2 virus infection in a subject is provided, which comprises a codon optimized polynucleotide sequence encoding a polypeptide of the SARS-CoV-2 virus. The invention also provides a vaccine combination for resisting SARS-CoV-2 virus infection, and the vaccine combination comprises the DNA vaccine and an antigen peptide vaccine. In the NHP research, the vaccine composition can endow comprehensive protection against SARS-CoV-2 virus infection. 提供了在受试者中抗SARS-CoV-2病毒感染的DNA疫苗，其包含编码SARS-CoV-2病毒的多肽的经密码子优化的多核苷酸序列。还提供了抗SARS-CoV-2病毒感染的疫苗组合，其包含所述DNA疫苗和抗原肽疫苗。在NHP研究中，该疫苗组合能够赋予抗SARS-CoV-2病毒感染的全面保护。